Carba Analogues of Flupirtine and Retigabine with Improved Oxidation Resistance and Reduced Risk of Quinoid Metabolite Formation. (7th July 2022) - Wurm, Konrad W.; Bartz, Frieda‐Marie; Schulig, Lukas; Bodtke, Anja; Bednarski, Patrick J.; Link, Andreas
Abstract: The KV 7 potassium channel openers flupirtine and retigabine have been valuable options in the therapy of pain and epilepsy. However, as a result of adverse reactions, both drugs are currently no longer in therapeutic use. The flupirtine‐induced liver injury and the retigabine linked tissue discolouration do not appear related at first glance; nevertheless, both events can be attributed to the triaminoaryl scaffold, which is affected by oxidation leading to elusive reactive quinone diimine or azaquinone diimine metabolites. Since the mechanism of action, i. e. KV 7 channel opening, seems not to be involved in toxicity, this study aimed to further develop safer replacements for flupirtine and retigabine. In a ligand‐based design strategy, replacing amino substituents of the triaminoaryl core with alkyl substituents led to carba analogues with improved oxidation resistance and negligible risk of quinoid metabolite formation. In addition to these improved safety features, some of the novel analogues exhibited significantly improved KV 7.2/3 channel opening activity, indicated by an up to 13‐fold increase in potency and an efficacy of up to 176 % compared to flupirtine, thus being attractive candidates for further development. Abstract : With the aim of providing safer replacements for the KV 7 potassium channel openers flupirtine and retigabine, the oxidation‐sensitive triaminoaryl scaffold was modified in a ligand‐based approach in order to obtain oxidation‐resistant carba derivatives. Some of these novel analogues have a negligible risk for the formation of quinoid metabolites and possess potent KV 7.2/3 opening activity.